Brazilian Spotted Fever with an Approach in Veterinary Medicine and One Health Perspective - Sabrina Destri Emmerick Campos; Nathalie Costa da Cunha; Nádia Regina Pereira Almosny (Veterinary Medicine International)
There is increasing interaction between man and pathogens transmitted by arthropods, especially by ticks. It is on this background that a holistic approach stands out, for the sake of Public Health. Brazilian Spotted Fever is an endemic disease at the country’s southeast, with Amblyomma sculptum as its major contributor, followed by A. aureolatum and potentially Rhipicephalus sanguineus. Dogs have been considered sentinels, and in some areas the disease in dogs can precede human disease. Considering the importance of this disease for human health, the serological evidence in dogs, and the transmission of ticks between dogs and their owners, this review aimed to elucidate the importance of the epidemiological investigation, the diagnosis in dogs, and the role of veterinarians in Public Health to control vector-borne zoonotic diseases. We encourage veterinarians to include this rickettsial infection in the diagnosis of febrile diseases of common occurrence in dogs.